Targeting of Low-Dose CT Screening According to the Risk of Lung-Cancer Death - Kovalchik, Stephanie A; Tammemagi, Martin; Berg, Christine D; Caporaso, Neil E; Riley, Tom L; Korch, Mary; Silvestri, Gerard A; Chaturvedi, Anil K; Katki, Hormuzd A (The New England journal of medicine, 2013)
The 60% of patients at highest risk for lung cancer in the National Lung Screening Trial accounted for 88% of the lung-cancer deaths prevented by low-dose CT screening. The use of risk assessment can improve the yield from low-dose CT screening for lung cancer. Lung cancer is the most common cause of cancer-related death in the United States, accounting for 28% and 26% of all cancer deaths among men and women, respectively. 1 Recent results from the National Lung Screening Trial (NLST), which showed a 20% reduction in lung-cancer mortality with low-dose computed tomography (CT) screening, as compared with chest radiography, highlighted the opportunity to reduce the burden of death from lung cancer. 2 With 94 million current and former smokers in the United States, 3 deciding which smokers to target for low-dose CT screening remains an important public health challenge, given the potential costs and harms . . .